Associations of gestational and early life exposure to air pollution with childhood allergic rhinitis. (1st March 2019) - Huang, Qing; Ren, Yunzhao; Liu, Yisi; Liu, Suyang; Liu, Feifei; Li, Xiangyu; Li, Baojing; Hou, Yitan; Lu, Yuanan; Li, Shiyue; Yan, Hong; Xiang, Hao
Abstract: Emerging researches found that air pollution had some effects on childhood allergic rhinitis, but the associations between gestational and early life exposure to air pollution and childhood allergic rhinitis are unclear. This study aimed to analyze the association between gestational and early life exposure to air pollutants and childhood allergic rhinitis. There are 3165 preschool children from Wuhan and Ezhou during November to December 2017. Parents or guardians reported information on childhood allergic rhinitis, lifestyle, the health status of children and family members. The concentration of NO2, PM2.5, and PM10 (2011–2016) were estimated by a spatiotemporal model with satellite remote sensing and land use information. We used binary logistic regression models to estimate adjusted odds ratio (aOR) and 95% confidence intervals (95%CI) for 1 μg/m 3 of increase in each air pollutant during pregnancy and early life. We found that 639 (20.2%) children were diagnosed as allergic rhinitis among 3165 children. After adjusting for covariates, exposure to air pollution during pregnancy and the first year of life were significantly associated with childhood allergic rhinitis. Excessive exposure to PM2.5 and PM10 both increased the prevalence of childhood allergic rhinitis during pregnancy (PM2.5 : aOR = 1.232, 95%CI: 1.201–1.263; PM10 : aOR = 1.063, 95%CI: 1.052–1.075) and in the first year of life (PM2.5 : aOR = 1.032, 95%CI: 1.006–1.059; PM10 : aOR = 1.018, 95%CI: 1.005–1.031). The relationship of exposure to NO2 and childhood allergic rhinitis was only significant for exposure during the first year of life (aOR = 1.013, 95%CI: 1.002–1.025). In summary, our findings suggested that gestational and early life exposure to air pollution is a risk factor for childhood allergic rhinitis. Highlights: Gestational and early life exposure to air pollution is a risk factor. The effects of gestational exposure on childhood allergic rhinitis are strong. The effects of exposure to PM on childhood allergic rhinitis are strong.